Overview of Asymmetric Warfare Strategy and International Relations in the Syrian War 2011 - Wibowo, Haryanto (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2023)
This article focuses on analyzing the Asymmetric War carried out by the parties involved in the Syrian War. The actors analyzed were the state, the opposition, and the pro-revolutionary parties. With a qualitative approach, this study emphasizes content analysis methods. The framework of this research departs from the conflict in Syria which can be analyzed by the theory of Asymmetric Warfare by Rod Thornton and the theory of International Relations. The research results show that the conflict in Syria is part of Asymmetric Warfare, i.e. the support of military forces by foreign countries in the Syrian War conflict is urgently needed by each side (pro-revolutionary and pro-regime). In addition, viewed from international relations was a continuation of the Cold War launched by a great power country between Russia and the United States. It is therefore essential to undertake a thorough investigation of the current evolution of Modern War, particularly Asymmetric War.